1999
DOI: 10.1161/01.cir.99.7.889
|View full text |Cite|
|
Sign up to set email alerts
|

Enteroviral RNA Replication in the Myocardium of Patients With Left Ventricular Dysfunction and Clinically Suspected Myocarditis

Abstract: These data demonstrate that a significant fraction of patients with left ventricular dysfunction and clinically suspected myocarditis had active enteroviral RNA replication in their myocardium (22%). Differentiation between patients with active viral replication and latent viral persistence should be particularly important in future studies evaluating different therapeutic strategies. In addition, molecular genetic detection of enteroviral genome and differentiation between replicating versus persistent viruse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
122
1
7

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(134 citation statements)
references
References 19 publications
4
122
1
7
Order By: Relevance
“…When we do not consider the targeting of gene therapy vectors, but human diseases, the existence of significant CAR expression in lung, small intestine and heart is consistent with the respective illnesses caused by wildtype adenoviruses. [57][58][59][60] After attachment to the cell surface adenovirus is internalized via interaction of RGD sequences of the viral pentone base with cellular ␣ v ␤ 3 and ␣ v ␤ 5 -integrins. 40 The expression of integrins on the plasma membrane seems to be regulated through regulation of production of the ␣ chain since most cells express the ␤ chains in excess.…”
Section: Figure 9 Car-mrna Quantification In Different Tissues From Mmentioning
confidence: 99%
“…When we do not consider the targeting of gene therapy vectors, but human diseases, the existence of significant CAR expression in lung, small intestine and heart is consistent with the respective illnesses caused by wildtype adenoviruses. [57][58][59][60] After attachment to the cell surface adenovirus is internalized via interaction of RGD sequences of the viral pentone base with cellular ␣ v ␤ 3 and ␣ v ␤ 5 -integrins. 40 The expression of integrins on the plasma membrane seems to be regulated through regulation of production of the ␣ chain since most cells express the ␤ chains in excess.…”
Section: Figure 9 Car-mrna Quantification In Different Tissues From Mmentioning
confidence: 99%
“…PCR was performed with Elongase (Invitrogen), 5Ј-CAT-GGCGCTCCTGCTGTGCTTCGTGCTCCTGT-3Ј as primer P5Ј and 5Ј-AGGCTCTATACTATAGACCCAT-3Ј as P3Ј (1). PCR products were separated on a 1% low melting agarose gel, appropriate bands were excised, and CAR-specific sequences were re-amplified with P5Ј and P3Ј(2) 5Ј-AGGTGGGAGAGTCGGA-3Ј directly on aliquots of melted gel.…”
Section: Methodsmentioning
confidence: 99%
“…Coxsackie-and adenoviruses are well known pathogens in inflammatory and dilated cardiomyopathy (1,2). Both of these structurally unrelated viruses use the coxsackie-adenovirus receptor (CAR) 1 for cell attachment and internalization (3,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been suggested that some patients with IDC are also afflicted with insidious forms of viral myocarditis, through chronic inflammation mechanisms and self-immunity [5,6]. Evidence of viral participation is based on serology and/or the finding of viral DNA in the myocardium, demonstrated through PCR (polymerase chain reaction) techniques [7][8][9].…”
mentioning
confidence: 99%